Ethno-Ornithology Study and Identification of Community Local Wisdom in Conservation of Birds and their Habitat in Peudada District, Bireuen Regency - Nurul Syafina; Abdullah Abdullah; Mimie Saputri; Safrida Safrida; Devi Syafrianti (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
ABSTRACTEthno-ornithology was the study of various aspects of the use of birds from the perspective of knowledge and culture of society. This research was conducted from March 2020 to August 2020. The purpose of this study was to determine the various uses of bird species by the community in Peudada District, Bireuen Regency in terms of moral values. The method used is the semistructural interview method, with triangulation techniques, namely triangulation of methods and triangulation of data sources. This research was conducted in Peudada District with 15 villages consisting of 75 respondents. In each village 5 respondents consisted of 2 traditional leaders and 3 local people who knew information about birds that were often used by the community. The data were analyzed qualitatively and descriptively based on literature study. The results obtained 32 bird species with 18 uses by the Peudada District, Bireuen Regency. Utilization of bird species that have local wisdom for the people of Peudada Subdistrict are free-range chickens (Gallus sp.), serati ducks (Chairina moschata), forest lathes (Centropus rectunguis), buffalo starlings (Acridotheres javanicus), eagles (Aquila sp.), and manyar (Ploceus manyar). Keywords: Etno-ornitologi, Bird, Peudada District.ABSTRAKEtno-ornitologi adalah studi tentang berbagai pemanfaatan aspek burung dari sudut pandang pengetahuan dan budaya masyarakat. Penelitian ini telah dilaksanakan sejak Maret 2020 sampai Agustus 2020. Tujuan penelitian ini untuk mengetahui berbagai pemanfaatan jenis burung oleh masyarakat di Kecamatan Peudada, Kabupaten Bireuen ditinjau dari nilai moral. Metode yang digunakan adalah metode wawancara semistruktural, dengan teknik triangulasi yaitu triangulasi metode dan triangulasi sumber data. Penelitian ini dilakukan di Kecamatan Peudada dengan 15 desa yang terdiri dari 75 responden. Pada masing-masing desa ditetapkan 5 responden yang terdiri dari 2 orang tokoh adat dan 3 orang masyarakat setempat yang mengetahui informasi tentang burung yang sering dimanfaatkan oleh masyarakat. Data dianalisis secara kualitatif dan deskriptif berdasarkan studi pustaka. Hasil penelitian diperoleh 32 spesies burung dengan 18 pemanfaatan oleh masyarakat Kecamatan Peudada, Kabupaten Bireuen. Pemanfaatan jenis burung yang memiliki kearifan lokal bagi masyarakat Kecamatan Peudada adalah ayam kampung (Gallus sp.), itik serati (Chairina moschata), bubut hutan (Centropus rectunguis), jalak kerbau (Acridotheres javanicus), elang (Aquila sp.), dan manyar (Ploceus manyar). Kata Kunci: Etno-ornitologi, Burung, Kecamatan Peudada.